1991
DOI: 10.1111/j.1471-4159.1991.tb03801.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Partial Characterization of Angiotensin II Receptors from Rat Brain

Abstract: Rat brain angiotensin II (Ang II) receptors were solubilized with a yield of 30-40% using the synthetic detergent 3[(3-cholamidopropyl)dimethylammonio)]-1-propanesulfonate. Kinetic analysis employing the high-affinity antagonist 125I-Sar1,Ile8-Ang II indicated that the solubilized receptors exhibited the same properties as receptors present within intact brain membranes. Furthermore, there was a positive correlation (r = 0.99) between the respective pIC50 values of a series of agonist and antagonists competing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For instance, in previous studies AngIl receptors from rat brain (15) and from NlE-115 cells (14) have been successfully solubilized by using the zwitterionic de- (14). These studies revealed that the AT2 binding site has an apparent molecular mass of 66 kDa as estimated by covalent crosslinking and SDS/PAGE analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in previous studies AngIl receptors from rat brain (15) and from NlE-115 cells (14) have been successfully solubilized by using the zwitterionic de- (14). These studies revealed that the AT2 binding site has an apparent molecular mass of 66 kDa as estimated by covalent crosslinking and SDS/PAGE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have demonstrated the successful solubilization of functional AT2 receptors from NlE-115 cells by using the zwitterionic detergent 3-[(3-cholamidopropyl)dimethylammoniol-1-propanesulfonate (CHAPS) (14,15). These solubilized AT2 receptors retained their high affinity for 1251-labeled AngII (125I-AngII) and specificity for AT2-selective ligands.…”
mentioning
confidence: 99%
“…Previously, AT 1 receptor dimerization has been suggested by using various approaches. 1) Using Angiotensin affinity labeling, or chemical cross-linking experiments, AT 1 receptor complexes with a molecular weight corresponding to a dimeric complex have been identified in transfected cell lines and in several organs such as liver adrenal pituitary and brain (41)(42)(43)(44)(45). 2) High affinity ligand binding has been reconstituted by co-expression of two receptors (AT 1 -K102A and -K199A) that did not bind ligand when expressed individually (17).…”
Section: Discussionmentioning
confidence: 99%
“…These analyses showed that is was possible to identify AT1R receptor complexes with molecular weights corresponding to both a monomeric and a dimeric form of the receptor. However, these observations were not linked to any functional consequences, and it has been speculated, that the dimers could result from technical artefacts causing protein aggregation (9,23,(49)(50)(51)(52)(53).…”
Section: At1 Receptor Activation and Signallingmentioning
confidence: 99%